Flow Field Predictions of Bluff Body Introduced Micro Combustor. (2016) - Sarath, C.G.; Sreejith, M.; Reji, R.V.
Abstract: Combustion in micro scale is the area having wide scope in this era of miniaturization of energy efficient devices. Some important areas of application are in the field of propulsion as a micro thruster and as an apt replacement for conventional batteries by accounting the high energy density of micro combustors. Numerical simulation of combustion is a challenging process due to associated chemical reaction, unsteadiness and non equilibrium nature. In this work a numerical study has been carried out in a typical non premixed micro combustor. The steady simulations of micro combustor without and with bluff body are analyzed for different fuel inlet velocities. For studying the effect of location of bluff body, the micro combustor with wall positioned bluff body is separately analyzed by changing the position of bluff body along axial direction. The effect of different bluff body shapes and significance on its location in combustion process is analyzed. The results are presented in the form of contours of velocity, temperature and mass fractions.